HUBUNGAN EMPATI DENGAN PERILAKU ALTRUISTIK - Ni'mah, Roudlotun (Universitas Nahdlatul Ulama Sunan Giri, 2017)
“This study aims to determine the relathionship between empathy with altruistic behavior. Subjects were students in Al-asy’ari boarding school totaling 90 student for male sex between the age of 12 to 25 years. Meansuring intruments used are altruistic behavior scale and empathy scale. The data capture techniques using proportionate stratified random sampling. Methods of data analysis using regression analisysis with SPSS16.0 program. The resulst showed positive significant relationship between empathy and altruistic behavior. Effective contribution of empathy to altruistic behavior for students in Al-asy’ari boarding school is 44% indicated by the coefficient of determinant (R2) 44,0. This means there is 66,4% of other variables that affect students’ altruistic behavior.”